A Contrastive Analysis Of The Use Of Hedges In English And Arabic Newspaper Editorials - Nesba, Kaouther (University of Eloued جامعة الوادي, 2024)
The study investigates hedging in Arabic and English newspaper editorials, examining differences in usage and types. It analyzes 60 editorials from two Arabic (Echorouk and Elkhabar) and two British English newspapers (The Independent and The Guardian), applying Salager-Meyer’s (1997) model. Results indicate hedging in both languages, with English utilizing more hedges. Arabic leans towards approximators of degree, quantity, frequency, and time, while English favors modal auxiliary verbs. The study underscores the importance of teaching learners not only grammar but also rhetorical structures across different writing genres. تتناول الدراسة استخدام الاحتياطات في افتتاحيات الصحف العربية والإنجليزية، ودراسة الاختلافات في الاستخدام وأنواعها. قامت بتحليل 60 مقالة افتتاحية من صحيفتين عربيتين (الشروق والخبر) وصحيفتين بريطانيتين باللغة الإنجليزية (الإندبندنت والجارديان)، مطبقة نموذج سالجر ماير(1997). تشيرالنتائج إلى استخدام الاحتياطات في كلتا اللغتين، مع استخدام اللغة الإنجليزية لمزيد من الاحتياطات. تميل اللغة العربية نحو تقريب الدرجة والكمية والتكرار والوقت، بينما تفضل اللغة الإنجليزية الأفعال المساعدة الشرطية. تسلط الدراسة الضوء على أهمية تعليم المتعلمين ليس فقط قواعد اللغة ولكن أيضًا الهياكل البلاغية عبر أنواع الكتابة المختلفة.
Article. Ex Professo. Vol 09. N.01 .University of El oued
Keywords: Arabic; Editorials; English; Hedges; Newspapers